2023
DOI: 10.1097/qad.0000000000003481
|View full text |Cite
|
Sign up to set email alerts
|

Lower anti-Müllerian hormone levels are associated with HIV in reproductive age women and shorter leukocyte telomere length among late reproductive age women

Abstract: Objectives:We sought to better understand factors associated with ovarian aging in women with HIV (WWH).Design:HIV has been associated with diminished fertility, younger age at menopause, and shorter leukocyte telomere length (LTL), a marker of cellular aging. We herein examine cross-sectional and longitudinal associations between LTL, anti-Müllerian hormone (AMH), and HIV.Methods:We included WWH and HIV-negative women 12–50 years of age in the CARMA cohort with one or more study visit(s). LTL and AMH were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, three studies did assess whether women living with HIV were more likely to have very low AMH (i.e., below a certain cut-point) compared with HIV-negative women. Consensus on the exact cut-point that constitutes low AMH is lacking; indeed, different cut-points ranging from less than 7.1 to 14.3 pmol/L have been used to define low AMH [28,29]. Merlini et al [15] found that women living with HIV had greater odds of low AMH (<7.1 pmol/L) than did HIV-negative women after adjusting for age and smoking status (adjusted odds ratio 3.9 [95% CI 1.73-8.90]; p = 0.01).…”
Section: Author Yearmentioning
confidence: 99%
“…However, three studies did assess whether women living with HIV were more likely to have very low AMH (i.e., below a certain cut-point) compared with HIV-negative women. Consensus on the exact cut-point that constitutes low AMH is lacking; indeed, different cut-points ranging from less than 7.1 to 14.3 pmol/L have been used to define low AMH [28,29]. Merlini et al [15] found that women living with HIV had greater odds of low AMH (<7.1 pmol/L) than did HIV-negative women after adjusting for age and smoking status (adjusted odds ratio 3.9 [95% CI 1.73-8.90]; p = 0.01).…”
Section: Author Yearmentioning
confidence: 99%